Investigating Implementation of Project-Based Learning in Middle Schools Math Classes Within Baku Public Schools - Ismayilzada, Fidan; Karimli, Gulustan; Aghayeva, Aysun (My University, 2026)
This qualitative study explores teachers’ and administrators’ perceptions and experiences regarding the implementation of Project-Based Learning (PBL) in middle-school mathematics classrooms within Baku public schools. Grounded in constructivist learning theories, including experiential learning (Kolb, 1999), cognitive constructivism (Piaget), and social constructivism (Vygotsky), the study examines participants’ comprehension of PBL, its implementation practices, perceived benefits, contextual challenges, and institutional support. The participants included six middle-school mathematics teachers and three school administrators from three public schools in Baku. Data were collected through semi-structured interviews and analyzed using Braun and Clarke’s (2025) thematic analysis framework. The findings identified four main themes: differing levels of understanding and implementation of PBL, positive perceptions regarding PBL implementation, structural and contextual challenges affecting implementation, and institutional support and professional development needs. The findings suggest that although participants generally viewed PBL positively and associated it with increased student engagement, collaboration, and real-life learning, its implementation remained limited due to curriculum intensity, exam-oriented systems, limited resources, and insufficient professional development opportunities. By exploring PBL implementation within the context of Baku public schools, this study addresses a gap in the existing literature and provides context-specific insights for mathematics education. The findings may support teachers, school leaders, and policymakers in strengthening student-centered instructional practices and promoting more effective implementation of PBL in Azerbaijani public schools.
Keywords: Project-Based Learning; Teachers' Perceptions; administrators' perceptions; Baku public schools